Why some firms succeed in exporting while others do not? The impact of resources and capabilities on firms' export performance - Simões, Luís Carlos Ganhão (2013)
Dissertação de Mestrado em Negócios Internacionais apresentada à ESTG - Escola Superior de Tecnologia e Gestão do Instituto Politécnico de Leiria.